Optimalisasi Model Brain-Based Learning dengan Media AI Plant Net Identifier dalam Meningkatkan Minat Belajar dan Keterampilan Berargumentasi Siswa SMA - Purnamasari, Nuraida Delia; Prihatin, Jekti; Siswati, Bea Hana (Jurnal Inovasi Pembelajaran Biologi, 2025)
Biology learning is a study of science with complex material, making it difficult for students to understand and reducing their interest and motivation to learn. Therefore, engaging and meaningful learning methods, such as the Brain-Based Learning (BBL) model using the AI Plant Net Identifier media, are needed. This study aimed to determine the effect of the BBL model using the AI Plant Net Identifier media on students' learning interest and argumentative skills. The research method employed a quantitative quasi-experimental method involving two classes: an experimental class and a control class. Data analysis was conducted using ANACOVA tests for learning interest and argumentative skills. Learning interest obtained a significance value of 0.011, while argumentation skills obtained a significance value of 0.000. Thus, it was concluded that the Brain-Based Learning model using the AI Plant Net Identifier media influenced students' learning interest and argumentation skills. The average scores obtained in the experimental and control classes for learning interest were 62.4, categorized as interested, and 57.7, categorized as moderately interested. The average scores for argumentation skills in the experimental and control classes were 71.4, categorized as high, and 60.5, categorized as moderate.